A Competitiveness Analysis of Durres City - Golgota, Boriana; Golgota, Alma; Spahiu, Ermal (Mediterranean Journal of Social Sciences, 2012)
This paper takes in consideration our hometown city, Durres. It is the second largest city of Albania, and the mostancient one. Durres is located in the north-western part of the Western Lowland of Albania. The historical development of the cityof Durres is rooted in early connection with other Albanian and foreign cities, because of its suitable location in the region. Theport of Durres is the biggest port in Albania, in which export and import processes is regularly handled. This paper includes ahistorical analysis of Durres city, looked under city’s development since the period after the World War II until nowadays. Asmany other major Albanian cities, Durres has passed through an uncontrolled urban development in the last twenty years. Thechange of mono system into pluralism, from 1990, and the application of the economical reforms of the trade were accompaniedwith the appearance of many problems. Regarding to the urban city transformation, the period of transition led to a high cityurban growth and densification. Illegal buildings were constructed in previously green areas, such as in the old beach. Is thisuncontrolled urban development also influenced the informal settlements in industrial zones, such as the one in Spitalla, PortoRomano, and Keneta. Ongoing these deep change processes, unemployment rate has suffered significant decline. Through atable we can demostate the city life cycle of Durres city. Moreover, analyzing the competitive capacities of Durres, we make acompetitiveness analysis of Durres city with two other national and regional competitive cities: Tirana and Istanbul, highlightingthe stong and weak points of these capitals.